Strategic Competencies of Prospective Teacher Students Based on Cognitive Style and Gender - Andi Syukriani (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2023)
This study aims to describe the strategic competencies of prospective teacher students based on cognitive style and gender in formulating, representing and solving problems. This type of research was descriptive qualitative. The supporting instruments were the GEFT (Group Embedded Figure Test) and the task of mathematical non routine problem contained several mathematical concepts, namely circles, trigonometry, and triangles. The research subjects consisted of 2 males Field Independent (FI) and 2 females Field Independent (FI), 6 females Field Dependent (FD) and 4 males Field Dependent (FD). Data was collected through documentation of solving mathematical problem and interview results. The data validity method used method triangulation and referencial adequacy checks. Research datas were analyzed by reducing data, presenting data and drawing conclusions. The results showed that FI females and males were more analytical than FD females and males. FI males and FI females both understood problem situations by drawing, but FI males recognized the circle concept more quickly and confidently than FI females. FI females were more analytical in the process of transferring problem situations into pictures than FI males. FI males and FI females both represented problem situations in pictures and symbols but FI females tended to have more logical pictures and symbols than FI males. FD females tended to understand problem situations by drawing more than FD males, therefore FD females were said to be more analytical in transferring problem situations into pictures compared to FD males. The four types of subjects did not arrive at a correct final solution.